'Dulce et decorum est pro patria mori': the practical and symbolic treatment of the Roman war dead. (2nd January 2018) - Hope, Valerie Margaret
Abstract: In literary sources death in Roman battle was often portrayed as glorious, yet how the bodies of the war dead were treated was far removed from this ideal. This paper focuses on this dichotomy, and the seeming contradictions in attitudes and behaviours. In ancient Rome, the war dead were little remembered, respected and mourned for. After battle the bodies of dead soldiers were hastily gathered and disposed of en masse. There were no war memorials that listed the names of the dead, no military war cemeteries that acted as places of pilgrimage, little battlefield tourism and no annual commemorative rituals. This stands in stark contrast to the tombstones set up by soldiers in peacetime, to the arches and columns that celebrated victories in the city of Rome, to the triumphal processions that filled its streets and the tales of military bravery that formed literary set pieces. On the one hand to die for Rome was presented as glorious, on the other hand the reality was bloody, brutal and seemingly soon forgotten. This paper investigates how the bodies of soldiers were treated post-battle, uniting the limited archaeological evidence with a range of literary texts. Why was the basic treatment of military corpses deemed acceptable, and how were those corpses manipulated in real, and literary, games of power and politics?